PENGARUH LIKUIDITAS DAN PROFITABILITAS TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN MANUFAKTUR : Current Ratio, Net Profit Margin, Return on Assets, Profit Growth - Ulum, Bustanul (GEMA EKONOMI, 2020)
This study aims to determine and analyze the effect of Current Ratio, Net Profit Margin, and Return On Asset on profit growth in Food and Beverages listed on the Indonesia Stock Exchange (IDX) during the 2016 - 2018 period. The method used is multiple linear regression analysis, by performing the classical assumption test, hypothesis testing and the coefficient of determination. The results obtained partially, Current Ratio has an effect on profit growth, Net Profit Margin has an effect on profit growth, and Return on Assets has an effect on profit growth. While simultaneously Current Ratio, Net Profit Margin, and Return on Assets have an effect on profit growth.